Validation of the Skindex-17 quality of life assessment instrument for a Brazilian population - Scotton Jorge, Marilia Formentini [UNESP]; Mourao, Ioana Bittencourt [UNESP]; Pollo, Camila Fernandes [UNESP]; Sousa, Ticiane Dionizio de [UNESP]; Meneguin, Silmara [UNESP]; Miot, Helio Amante [UNESP] (Elsevier B.V., 2021)
Background: Health-related quality of life assesses how diseases affect the daily life of people; there are several generic instruments for this assessment in dermatology. Skindex was created in 1996; it is a multidimensional instrument, aiming to encompass some psychological and social aspects not yet addressed by other questionnaires. Among its versions (Skindex-29, 16, and 17), Skindex-17 had not been validated in Brazil. Objectives: To validate Skindex-17 for use in Brazilians with dermatological diseases. Methods: This was a methodological, cross-sectional, and prospective study of 217 patients attended at the Dermatology Service Outpatient Clinic, Faculdade de Medicina de Botucatu - Universidade Estadual Paulista (Botucatu, SP, Brazil), from December 2017 to September 2019. The following were evaluated: content validity, filling time, internal consistency, dimensional structure, concurrent validity (DLQI), temporal stability, and responsiveness. Results: The sample consisted of 71% women, mean age (SD) of 45 (16) years; phototypes II-IV accounted for 95% of the cases. Cronbach's alpha coefficients were 0.82 and 0.93 for the symptoms and psychosocial conditions, respectively. A high correlation was observed with the DLQI score: symptoms (rho =0.69) and psychosocial conditions (rho = 0.75). The instrument's two-dimensional structure was confirmed through confirmatory factor analysis. Temporal stability (ICC > 0.9) and score responsiveness (p <= 0.02) were verified. The instrument was shown to be feasible in clinical practice due to the content validation performed by professionals and patients, as well as the low time spent completing it (< 5 min). Study limitations: Single-center study, with patients exclusively from the public healthcare system. Conclusions: Skindex-17 was shown to be a valid and consistent instrument for assessing quality of life among patients with dermatological diseases, in Brazil. Its two-dimensional structure was confirmed. (C) 2020 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Dermatology; Indicators of quality of life; Psychometrics; Quality of life